A centennial tribute to the Politzer Acoumeter. (2nd April 2020) - Young, John Riddington; Mudry, Albert
Abstract: Objective: This year (2020) is the centenary of the death of the great otologist, Adam Politzer (1835–1920), the Founding Father of Otology. As a centennial tribute to him, the origin and development of his acoumeter is presented. Method: historical study based exclusively on primary sources. Results: Invented by Politzer in 1877, this small portable device to test auditory acuity was quickly accepted by colleagues and remained in popular use for more than 50 years. A detailed account of the Politzer Acoumeter is given together with a comparison with similar contemporary devices, which were also commercially available for clinical hearing testing. Conclusion: There is no doubt that the Politzer Acoumeter had given the electrical audiometer a good run. For more than half a century, it had been widely used and had proved to be a very useful test of hearing.